The influence of organizational injustice in the motivation for the practice of cybercrimes - Silva de Garcia, Plínio; Macadar, Marie Anne; Luciano, Edimara Mezzomo (Journal of Information Systems and Technology Management, 2018)
A influência do contexto organizacional na motivação para a prática de crimes cibernéticosEsta pesquisa analisou como a percepção de injustiça organizacional motiva a prática de crimes cibernéticos no local de trabalho. Em uma investigação qualitativa e exploratória, foram realizadas entrevistas com 16 especialistas em segurança cibernética. Os dados foram analisados através da técnica de análise de conteúdo categorial. Os resultados sugerem que a percepção de injustiça produz sentimentos negativos como a baixa-estima, a frustração e a ausência de culpa, e que essas emoções motivam a prática de crimes cibernéticos. Diferentes percepções identificadas entre os entrevistados deste estudo, associadas à revisão da literatura referente ao tema, permitiram a proposição de um modelo conceitual.The influence of organizational injustice in the motivation for the practice of cybercrimesThis research analyzes how the perception of organizational injustice motivates the practice of cybercrimes in the workplace. In a qualitative and exploratory investigation, interviews have been carried out for 16 specialists in cybernetic security. Data were analyzed through the categorical content analysis technique. The results obtained suggest that the perception of injustice produces negative feelings, such as low self-esteem, frustration, and lack of guilt, and these emotions, in turn, motivate the practice of cybercrimes. Different perceptions have been identified among the interviewees of this study, which are associated with the literature review related to the theme, allowed the proposition of a conceptual model.